Rapid growth rates of aerobic anoxygenic phototrophs in the ocean - Koblízek, Michal; Masín, Michal; Ras, Josephine; Poulton, Alex J; Prásil, Ondrej (Environmental microbiology, 2007)
We analysed bacteriochlorophyll diel changes to assess growth rates of aerobic anoxygenic phototrophs in the euphotic zone across the Atlantic Ocean. The survey performed during Atlantic Meridional Transect cruise 16 has shown that bacteriochlorophyll in the North Atlantic Gyre cycles at rates of 0.91-1.08 day(-1) and in the South Atlantic at rates of 0.72-0.89 day(-1). In contrast, in the more productive equatorial region and North Atlantic it cycled at rates of up to 2.13 day(-1). These results suggest that bacteriochlorophyll-containing bacteria in the euphotic zone of the oligotrophic gyres grow at rates of about one division per day and in the more productive regions up to three divisions per day. This is in striking contrast with the relatively slow growth rates of the total bacterial community. Thus, aerobic anoxygenic phototrophs appear to be a very dynamic part of the marine microbial community and due to their rapid growth, they are likely to be larger sinks for dissolved organic matter than their abundance alone would predict.
Keywords: Photosynthesis; bakteriochlorofyly; Chromatography, High Pressure Liquid; Atlantský oceán; anaerobióza; Anaerobiosis; aerobní bakterie; Atlantic Ocean; fotosyntéza; mořská voda; Phototrophic Processes; Bacteria, Aerobic; Seawater; vysokoúčinná kapalinová chromatografie; fototrofní procesy; Bacteriochlorophylls